Plan integral de gestión y prevención de riesgos laborales para la Empresa Andina de Proyectos ADPEC.S.A.S, para la seguridad de sus colaboradores y la minimización de accidentes. - Calderón Moran, Milton Javier (2024)
The present investigation was carried out to analyze the company “Andina of Proyects ADPEC S.A.S”, it does not have adequate technical management of occupational risks. Therefore, it focused on the ISO 45001:2018 standard necessary for the designing a Health and Safety Management System for all areas, it provided support and knowledge through security parameters established by the IESS for a safe work environment. Chapter I established the company's problems, which identified the lack of an internal safety regulation and the safety committee, the lack of a safe work manual, and the lack of knowledge of legal workplace safety regulations in the country, as well as the absence of standards, techniques and security elements of the company ADPEC.S.A.S, establishing the objectives and the respective justification. Chapter II developed the state of the art and practice, considering the investigative background from the theoretical and legal foundation of the investigation and the knowledge necessary to solve the problem posed. Chapter III developed the methodological design to be used, taking into account the technical approach embodied in descriptive and field research, determining the findings of the technical tools, such as the interview, survey, and direct observation, within the qualitative-quantitative approach, choosing a population. of 14 elements. Chapter IV analyzed and discussed the results based on their interpretation obtained through the applied tools. Chapter V established the proposal: Technical Management of Occupational Risks for the Prevention of Accidents and Occupational Diseases in the company Andina of Proyects ADPEC S.A.S, contributing to the safety of collaborators and the minimization of work accidents. The intended impact is to generate a culture of risk and accident prevention that may arise due to workers' ignorance or lack of discipline when carrying out their daily work.